Nutritional Status of Toddler Children in Cikoang Village, Mangarabombang District, Takalar District - Nurbaya Busthanul; M. Saleh S. Ali; Masyhur Syafiuddin; Rahmawati A. Nadja; Siti Hardiyanti Syam; Nabilah Rahmawati (Hasanuddin University, 2023)
Nutritional status is the end result of the balance between the food that enters the body (nutrient input) and the body's need (nutrient output) for those nutrients. In other words, the state of the body as a result of food consumption and the use of nutrients. Nutrient requirements are determined by many factors, including: basal metabolic rate, growth rate, physical activity, and relative factors, namely: ingestion, differences in absorption, utilization, and differences in excretion and destruction of nutrients in the body. A sample of 82 children aged between 2.5 and 5.0 years and 114 households representing adulthood was observed in two villages with Maudu' rituals, and 99 and 134 households in two villages without Maudu' rituals. The research was conducted in Cikoang Village, Takalar District. The results of this study indicate that the nutritional status of children under five in Cikoang Village is not good and needs attention from related parties in helping to improve child nutrition in Cikoang Village.